The Role of Behavioral Factors on Investment Decision Making: Moderating Role of Financial Literacy - Butt, Haris; Sajjad, Ali; Awan, Khurram Zafar; Shakil, Muhammad Haseeb (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this paper is to examine the impact of behavioral finance factors on stock market investment behavior. Moreover, it also determines the moderating role of financial literacy in behavioral finance factors and stock investment in Pakistan. Studies have been conducted on Pakistan Stock market investors. Data has been collected through a structured questionnaire. The survey was performed among 165 investors in the Pakistan stock market. SPSS and Smart PLS 3.0 were used to test the hypotheses. The study concluded that Overconfidence, Herding, Loss Aversion, and Risk Perception significantly impacted the performance of Stock Investment decision-making. Moreover, Stock Investment decision-making was also moderated by Financial Literacy except for risk perception. The findings of this study would help to comprehend the behavior of investors in the Pakistan stock market. Moreover, to achieve favorable outcomes, investors must possess financial literacy about the stock market.